Comparative morphological evaluation of the effectiveness of some practices of light therapy in wound healing (experimental testing) - I. G. Motorina; V. V. Benemanski; G. G. Iushkov; L. K. Kulikov; M. M. Rasulov; O. G. Shukina; N. A. Malishkina (Acta Biomedica Scientifica)
The article provides information on the efficiency of thermal injury healing in animals (rabbits) under light therapy with «Bioptron», «Ricta», «Azor», 0KN-11M, BOP-4. An analysis has been done of the results of the morphological and planimetric research within 5-15 days after wounding. The factual data received have led to the conclusion that it is advisable to combine different physiotherapeutic practices in wound treatment. Synchronization of processes of an epitelization and maturing of granulyatsionny fabric allowed to recommend for appointment different lengths of waves of optical range in a certain sequence, beginning from ultra-violet beams of short, average range, then laser radiation of an infrared, red range, and also their combination, then to continue influence by the polarized light through standard periods (courses).